Assessment of Serum Sodium Status in Patients With Acute Confusional State Admitted in A Tertiary Care Hospital (Journal of Shaheed Suhrawardy Medical College, 2026)
Context: Acute confusional state (ACS) which is a frequent medical emergency among hospitalized patients is often associated with different factors, resulting from different etiologies. Electrolytic imbalance especially disturbance in sodium serum level, is considered one of the manageable factors in the management of ACS.Methodology: This cross-sectional observational study was conducted in the Department of Medicine, Shaheed Suhrawardy Medical College Hospital, Dhaka with a duration of six months. A total of 100 patients with clinically diagnosed ACS were enrolled. Each patient underwent clinical evaluation and various laboratory investigations including serum electrolytes measurement, with their consent. Data were analyzed using SPSS; p 0.05). Most patients (76%) recovered without sequelae; mortality was 6%.Conclusion: ACS is a common medical condition in tertiary level hospital of Bangladesh, where Hyponatremia is a common complication. Patients who develop ACS have high disability, complication rate and longer length of stay than any other patients. Knowing the nature and timing of the disease, together with the identification of high-risk patients are essential to reduce complications and improve outcome.J Shaheed Suhrawardy Med Coll 2024; 16(2): 63-68